KEBIJAKAN PEMERINTAH KABUPATEN BANGLI DALAM PERUMUSAN MANAJEMEN MITIGASI BENCANA ALAM DI KECAMATAN KINTAMANI KABUPATEN BANGLI - sari, ita purnama (Magister Administrasi Publik Program Pascasarjana Universitas Ngurah Rai, 2024)
Bangli Regency, from its historical records, has experienced seven types of disasters. The seven types of hazards are volcanic eruptions (Mount Batur), earthquakes, landslides, forest and land fires, extreme weather, droughts, flash floods, and the COVID-19 pandemic has also occurred. Based on historical data of disaster events that occurred in Bangli Regency during the period of 2018-June 2021, there were 255 recorded disaster events. The research method used in this study is descriptive research with a qualitative focus. Qualitative approaches can be used to find out what is happening behind phenomena that are not well understood. The researcher obtained data and information through two methods to answer the research question, namely: (1) primary data collection through in-depth interviews; and (2) secondary data collection through literature and documentary studies.The results Wthis study indicate that disaster preparedness, particularly in disaster management, must be conducted in a structured manner to prevent or prepare for disasters. Knowledge about risks is crucial to educate the community and motivate individuals so that they prioritize the need for early warning systems and the preparation of steps to be taken when signs of an impending disaster begin to appear. Warning services for hazards must be issued by agencies or institutions that have the responsibility and authority. Keywords : Public Policy, Formulation, Implementation